Horrid Henry wakes the dead - Simon, Francesca; Ross, Tony (London : Orion Children's Books, 2016)
"Henry will do anything to win the grand prize at this year's talent show-- even wake the dead! Plus three other stories that will leave you screaming for more"--P. [4] of cover.
Horrid Henry and the TV remote -- Horrid Henry's school election -- Horrid Henry's bad present -- Horrid Henry wakes the dead.
"4 laugh-out-loud stories!"--Cover.
"Originally published in Great Britain in 2009 by Orion Children's Books"--T.p. verso.
Ages 7-10.
English language and literature.
Keywords: Horrid Henry -- (Fictitious character) -- Juvenile fiction; Horrid Henry -- (Fictitious character) -- Fiction; Conduct of life -- Juvenile fiction; Behavior -- Fiction; Humorous stories; Human behavior -- Fiction; Talent shows -- Fiction; Children's stories; Short stories; Humorous fiction